ITGA5 Predicts Dual-Drug Resistance to Temozolomide and Bevacizumab in Glioma - Shi, Ying; Wu, Mengwan; Liu, Yuyang; Hu, Lanlin; Wu, Hong; Xie, Lei; Liu, Zhiwei; Wu, Anhua; Chen, Ling; Xu, Chuan (Frontiers in Oncology, 2021)
Aims: Antiangiotherapy (Avastin) is currently regarded as a promising option for glioma patients who are resistant to TMZ treatment. But ongoing clinical research failed to meet therapeutic expectations. This study aims to explore the pivotal genetic feature responsible for TMZ and Avastin resistance in glioma patients. Methods: We downloaded transcriptomic and methylation data of glioma patients from TCGA, CGGA and GEO databases, grouped these patients into resistant and non-resistant group based on their clinical profiles. Differentially expressed genes and pathways were identified and exhibited with software in R platform. TMZ-resistant cell was constructed for validating expression change of candidate gene, ITGA5. ITGA5-overexpressing cell was also constructed to investigate its biological function by CCK8 assay, western blot, PAS staining and transcriptional sequencing. Results: Change of cell morphology and polarity was closely associated with TMZ mono-resistance and TMZ/Avastin dual-resistance in glioma patients. Expression level of ITGA5 was effective in determining drug resistance and glioma patients’ outcome, which is regulated by methylation on two distinct sites. ITGA5 was augmented in TMZ-resistant glioma cells, while overexpressing ITGA5 altered cell promoted TMZ resistance through enhancing VM formation correspondingly. Conclusions: Both epigenetic and transcriptional levels of ITGA5 are effective in predicting TMZ and Avastin resistance, indicating that ITGA5 may serve as a predictor of treatment outcome in glioma patients.